2011
DOI: 10.4269/ajtmh.2011.10-0177
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Identification of Trypanosoma cruzi Lineages in Human Infection Along the Endemic Area

Abstract: Genotyping studies show a polarized geographic distribution of Trypanosoma cruzi lineages in humans. Here, we assessed their distribution along Latin America through an immunological approach we designated Western blot (WB) assay with Trypomastigote small-surface antigen (TSSA) I and TSSA II (TSSA-WB). These antigens are expressed by T. cruzi I (TCI; now TcI) and T. cruzi II (TCII; reclassified as TcII to TcVI) parasites. TSSA-WB showed good concordance with genotyping tests. An unexpected frequency of TSSA II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…In Mexico, most T. cruzi strains have been genetically determined to belong to TcI (Bosseno et al 2002, Leó n-Pérez et al 2007, Gó mez-Hernández et al 2011 and TcII-TcVI strains have been reported only in a recent serological study, in wild mammals and the feces of vectors (Ló pez-Olmos et al 1998, Bosseno et al 2009, Risso et al 2011. In this work, we confirmed that the Mexican T. cruzi strains isolated from humans belonged to TcI, as reported in Guatemala, Colombia, and Venezuela (Añ ez et al 2004, Ruíz-Sánchez et al 2005, Falla et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…In Mexico, most T. cruzi strains have been genetically determined to belong to TcI (Bosseno et al 2002, Leó n-Pérez et al 2007, Gó mez-Hernández et al 2011 and TcII-TcVI strains have been reported only in a recent serological study, in wild mammals and the feces of vectors (Ló pez-Olmos et al 1998, Bosseno et al 2009, Risso et al 2011. In this work, we confirmed that the Mexican T. cruzi strains isolated from humans belonged to TcI, as reported in Guatemala, Colombia, and Venezuela (Añ ez et al 2004, Ruíz-Sánchez et al 2005, Falla et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…As previously shown (11), when used under more stringent conditions, a minimal fraction of Chagas-negative serum samples from patients affected by autoimmune and/or other endemic coinfection diseases reacted against bacterium-derived contaminants and/or the GST motif in TSSA-CL . On the other hand, p30-50 may contribute to improve the robustness of TSSA-based serologic methods in molecular epidemiology studies (17,18). The use of a more defined reagent lacking most of the sequences conserved across TSSA isoforms (14) may diminish its level of cross-recognition by antibodies elicited toward a different TSSA isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Interstrain polymorphisms were shown to be focused on the central region of TSSA (12,14) and to have a major impact on its immunogenicity and antigenicity (11,12,16). Different attempts at using TSSA polymorphisms to design parasite lineage-specific serologic reagents as an indirect approach to allow for the typification of infecting T. cruzi strains have been undertaken (17,18). Although these methods can be improved, they showed good concordance with genotyping techniques (17) and support the differential predominance of T. cruzi lineages causing human infections in distinct areas that are endemic for the parasite (13,19,20).…”
mentioning
confidence: 99%
“…The choice was based on previous results in which the TSSA isoform from DTU TcVI parasite stocks displayed a high reactivity with human infection sera from Southern Cone countries (15). Although the spectra of circulating parasite stocks, and therefore of their expressed TSSA isoforms, seem to vary in different areas of endemicity, a high frequency of TSSA VI recognition, as assessed by Western blotting, was also recently observed in patients with chronic Chagas' disease from Colombia, Venezuela, and Mexico (29). By using a much larger and more comprehensive serum panel, we estimated the overall sensitivity of GST-TSSA VI as 86.9% (Table 1).…”
Section: Discussionmentioning
confidence: 99%